The Charter of the City of Wilmington, at pt. 7, § 7 (1893) - (:unkn) unknown (My University, 1893)
Prohibited carry of firearms, shooting birds or other animals within the park, or throwing stones or missiles.
Keywords: SENSITIVE PLACES